2021
DOI: 10.3390/cancers13236045
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Distress Induces Wnt/β-Catenin Pathway Modulation in Colorectal Cancer Cells: Perspectives on APC Retained Functions

Abstract: Colorectal cancer (CRC) is a multistep process that arises in the colic tissue microenvironment. Oxidative stress plays a role in mediating CRC cell survival and progression, as well as promoting resistance to therapies. CRC progression is associated with Wnt/β-Catenin signaling dysregulation and loss of proper APC functions. Cancer recurrence/relapse has been attributed to altered ROS levels, produced in a cancerous microenvironment. The effect of oxidative distress on Wnt/β-Catenin signaling in the light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Meanwhile, we tested the EMT-related genes, such as E-cadherin, N-cadherin, vimentin, and Snail. The results showed that CBR-5884 exerts an antitumor effect through activating ROS/Wnt/ β -catenin pathway, which is consistent with the reported results in other malignant tumors [ 24 , 27 – 31 ]. At last, we verified the effect of CBR-5884 in vivo through nude mice xenograft.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, we tested the EMT-related genes, such as E-cadherin, N-cadherin, vimentin, and Snail. The results showed that CBR-5884 exerts an antitumor effect through activating ROS/Wnt/ β -catenin pathway, which is consistent with the reported results in other malignant tumors [ 24 , 27 – 31 ]. At last, we verified the effect of CBR-5884 in vivo through nude mice xenograft.…”
Section: Discussionsupporting
confidence: 91%
“…Reactive oxygen species which are produced by cell metabolic activities attach importance to cell signal transduction and homeostasis and regulate cell proliferation, apoptosis, and differentiation [24][25][26]. Recent studies suggested that oxidative stress induced by ROS can regulate Wnt/β-catenin signaling pathway in colorectal, breast, lung, pancreatic, and liver cancer [24,[27][28][29][30][31]. Therefore, studying the effect of CBR-5884 and NAC in the regulation of Wnt/β-catenin pathway is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Further experimental validation verified the synthetic lethal interaction of APC and GFER in a colon cancer cell line (Figs 5 and 6). APC , mostly known as a tumour suppressor involved in WNT signalling, is recurrently altered in colorectal cancer [45,46]. APC deficiency can activate a TCF4‐TDO2‐AhR‐CXCL5 circuit that impacts multiple cancer hallmarks via autonomous and non‐autonomous mechanisms, illuminating a genotype‐specific vulnerability in colorectal cancers [47].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, reactive radical-type oxygen species lead to the final formation of hydrogen peroxide (H 2 O 2 ), a highly diffusible molecule ( 39 ). This molecule produced by healthy cells is involved in multiple intracellular stress response signals ( 40 ). However, when H 2 O 2 is over-produced or inadequately detoxified, it can induce excessive intracellular production of 7,8-dihydro-8-oxoguanine (8-oxoG) ( 41 ).…”
Section: Introductionmentioning
confidence: 99%